PEDOMAN BISNIS YANG ETIS DAN RELATIVISME MORAL - Lukmono Hadi (Jurnal Ilmu Administrasi dan Bisnis, 2019)
This article aims to describe, through the theoretical moral relativism is the importance of ethics in business can be understood by the fact that ethical businesses tend to make much more than the others. The reason for this that customers of businesses which follow ethics are loyal and satisfied with the services and product offerings of such businesses. In this perspective, ethics involves concept of right and wrong, fair and unfari, moral and immoral. Belief about what is ethical serve as a moral compass in guiding the actions and behaviors of individuals and organization. Ethical principles in business are not materially offerent from ethical principal in general. Key word: ethical, business, moral relativism.